The Islamic Educational Philosophy of KH. Hasyim Asy'ari: Its Relevance and Implementation in the Context of Contemporary Education - Istiqomah, Istiqomah; Rosyada, Fahmushofa; Ibrahim, Rustam (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Education and Islam are closely intertwined as the foundation for shaping both worldly and spiritual life. The absence of character values, particularly morality, has led to a moral crisis in modern society. In this context, Islamic Religious Education (PAI) plays a crucial role as moral and ethical guidance, with significant contributions from Islamic figures such as KH. Hasyim Asy’ari, the founder of Nahdlatul Ulama and a reformer of Islamic education in Indonesia. This study aims to analyze KH. Hasyim Asy’ari's educational thoughts in shaping students' character and to examine their relevance to the moral and educational challenges in the era of globalization. Using a library research method with a qualitative approach, this research finds that KH. Hasyim Asy’ari's educational philosophy emphasizes a balance between religious and general knowledge, the cultivation of noble character, effective teaching methods, the role of teachers as mentors, and the importance of an educational environment rooted in Islamic values. These principles remain relevant in the digital era to address moral challenges such as intolerance and corruption while fostering a generation with strong character. In conclusion, KH. Hasyim Asy’ari's educational thoughts offer a solid foundation for Islamic education based on morality, making them a vital guide in modern education to tackle global challenges and ensure future generations possess noble character.